Near‐seabed sediment dynamics and fluxes on Chatham Rise, the effects of seabed disturbance, and implications for deep‐sea bottom trawling and seabed mining - Scott D. Nodder; Christopher A. Eager; Joe O’Callaghan; Daniel Leduc; Sam Davidson; Stacy Deppeler; Grace Frontin‐Rollet; Peter Gerring; Sarah Searson; William Quinn; Steve George; Ron Ovenden; et al. (New Zealand Journal of Marine and Freshwater Research, 2025)
Anthropogenic impacts are increasingly affecting deep‐sea environments, including seafloor sediment disturbances by bottom trawling and seafloor mining. Fieldwork in the ‘Resilience Of Benthic Ecosystems to Sedimentation’ (ROBES) project were conducted in 2018–2020 on the 400 m‐deep Chatham Rise crest, eastern Aotearoa New Zealand. Water column turbidity data, sediment traps on near‐seabed moorings and benthic landers and surficial sediments from multi‐corers provided baseline and post‐impact information following an artificially induced seafloor disturbance event in June 2019 using a modified harrow plough in and around an elongated bathymetric depression, designated as the ‘Butterknife’. During the disturbance, total mass and particulate organic carbon (POC) near‐bed fluxes were elevated above long‐term fluxes (2018–20). Long‐term 2018–19 fluxes were generally less than in 2019–20, driven by interannual oceanographic variations. These results, coupled with 50–100 m‐thick benthic boundary layers, suggest that lateral advection is a dominant process in the resuspension and redistribution of seafloor sediments on the rise. Further research is required to better understand the longer term dynamics of particle transport and deposition in response to human activities, such as bottom trawling or proposed phosphorite seafloor mining, especially in bathyal environments, such as the Chatham Rise.

Reduction in size of the calcifying phytoplankton Calcidiscus leptoporus to environmental changes between the Holocene and modern Subantarctic Southern Ocean - Andrés S. Rigual-Hernández; Gerald Langer; Francisco Javier Sierro; Helen Bostock; José Manuel Sánchez-Santos; Scott Davidson Nodder; Tom W. Trull; Anne Marie Ballegeer; Andrew D. Moy; Ruth Eriksen; Laura Makowka; Thibauld M. Béjard; et al. (Frontiers in Marine Science, 2023)
The Subantarctic Zone of the Southern Ocean plays a disproportionally large role on the Earth system. Model projections predict rapid environmental change in the coming decades, including ocean acidification, warming, and changes in nutrient supply which pose a serious risk for marine ecosystems. Yet despite the importance of the Subantarctic Zone, annual and inter-annual time series are extremely rare, leading to important uncertainties about the current state of its ecosystems and hindering predictions of future response to climate change. Moreover, as the longest observational time series available are only a few decades long, it remains unknown whether marine pelagic ecosystems have already responded to ongoing environmental change during the industrial era. Here, we take advantage of multiple sampling efforts – monitoring of surface layer water properties together with sediment trap, seafloor sediment and sediment core sampling – to reconstruct the modern and pre-industrial state of the keystone calcifying phytoplankton Calcidiscus leptoporus , central to the global marine carbonate cycle. Morphometric measurements reveal that modern C. leptoporus coccoliths are 15% lighter and 25% smaller than those preserved in the underlying Holocene-aged sediments. The cumulative effect of multiple environmental factors appears responsible for the coccolith size variations since the Last Deglaciation, with warming and ocean acidification most likely playing a predominant role during the industrial era. Notably, extrapolation of our results suggests a future reduction in cell and coccolith size which will have a negative impact on the efficiency of the biological pump in the Southern Ocean through a reduction of carbonate ballasting. Lastly, our results tentatively suggest that C. leptoporus coccolith size could be used as a palaeo-proxy for growth rate. Future culture experiments will be needed to test this hypothesis.